Attentional modulation of cell-class specific gamma-band synchronization in awake monkey area V4 - Vinck, Martin (2013)
Selective visual attention is subserved by selective neuronal synchronization, entailing precise orchestration among excitatory and inhibitory cells. We tentatively identified these as broad (BS) and narrow spiking (NS) cells and analyzed their synchronization to the local field potential in two macaque monkeys performing a selective visual attention task. Across cells, gamma phases scattered widely but were unaffected by stimulation or attention. During stimulation, NS cells lagged BS cells on average by ~60° and gamma synchronized twice as strongly. Attention enhanced and reduced the gamma locking of strongly and weakly activated cells, respectively. During a pre-stimulus attentional cue period, BS cells showed weak gamma synchronization, while NS cells gamma synchronized as strongly as with visual stimulation. These analyses reveal the cell-type specific dynamics of the gamma cycle in macaque visual cortex and suggest that attention affects neurons differentially depending on cell type and activation level.